Arabic Alphabet: Aplikasi Interaktif untuk Pembelajaran Bahasa Arab Anak Usia Dini - Abdul Qodir; Laili Mas Ulliyah Hasan (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This research explores the effectiveness of the interactive application "Arabic Alphabet" in learning Arabic for early childhood. This application is designed to introduce Arabic letters through a fun and interactive method, using various features such as educational games, audio pronunciations, and attractive visuals. This study uses a qualitative approach with a case study design involving 10 children aged 4-6 years, as well as the participation of their parents and teachers. Data was collected through observation, in-depth interviews and documentation for four weeks. Issues identified included technical challenges such as unresponsive touch screens and difficulty navigating within the app, as well as limited recommended screen time for children. Data analysis was carried out using the thematic analysis method, involving data transcription, coding, organizing themes, and interpretation. The validity and reliability of the research were maintained through source triangulation, member checking, and peer debriefing. Ethical aspects of the research were maintained by obtaining written consent from parents and teachers, maintaining confidentiality of participants' identities, and ensuring the welfare of children during the research process. The research results show that the "Arabic Alphabet" application is effective in increasing children's interest and involvement in learning Arabic. Children show high curiosity and interact more often with Arabic letters, and show progress in recognizing and pronouncing these letters. To overcome the obstacles found, the research recommends improving the technical features and navigation of the application as well as providing more comprehensive guidance for parents and teachers. The addition of a child progress monitoring feature is also recommended to provide more targeted and timely support. These findings provide deep insight into the effectiveness of apps in Arabic language learning and suggest recommendations for app developers, educators, and parents to improve children's learning experiences.